Utilization of 2D and 3D cell cultures for the modelling of intramammary infection in sheep - Dalaka, Eleni; Vassilakos, Demetrios; Stefos, Georgios C.; Kalogianni, Aphrodite I.; Palamidi, Irida; Gelasakis, Athanasios I.; Politis, Ioannis; Theodorou, Georgios (Frontiers in Animal Science, 2022)
Ovine mastitis is defined as the inflammation of the sheep udder, most commonly caused in response to intramammary infections. Based on the occurrence of clinical signs, mastitis is characterized as either clinical or subclinical (SCM). The impact of ovine SCM on the overall sustainability of dairy sheep farms has been substantially documented underpinning the significance of efficient diagnosis. Although SCM can be detected in cows, the performance and the validity of the methods used do not transfer in dairy sheep. This fact challenges the development of evidence-based ovine udder health management protocols and renders the detection and control of ovine mastitis rather problematic. Currently, cell culture-based models are being successfully used in biomedical studies and have also been effectively used in the case of bovine mastitis. The objective of the present study was to culture ovine primary mammary cells for the development of 2D and 3D cell culture-based models for the study of ovine mammary gland and to focus on the first stages of the intramammary infection by common mastitis-inducing pathogens. Cells were infected by E. coli and S. aureus mimicking the first stages of natural intramammary infections. The secreted proteins were subjected to mass-spectrometry resulting in the identification of a total of 79 distinct proteins. Among those, several had already been identified in healthy or mastitic milk, while others had not been previously detected for in the ovine mammary secretome. Our results suggest that the development of cell-based models for studying specific stages of intramammary infection the potential to be beneficial for the udder health management in dairy sheep.